Aquagenic Pruritus in Polycythemia Vera: Clinical Characteristics - Edyta Lelonek; Łukasz Matusiak; Tomasz Wróbel; Jacek C. Szepietowski (Medical Journals Sweden, 2018)
Aquagenic pruritus is one of the main clinical features of polycythemia vera. The aim of this study was to analyse the clinical characteristics of aquagenic pruritus. The study group comprised 102 patients with molecularly confirmed polycythemia vera. Demographic data, data on disease history, polycythemia vera status and treatment modalities were collected. Moreover, various clinical features of aquagenic pruritus (including intensity, localization, quality, descriptors) and the most common factors responsible for its aggravation or alleviation were examined. Aquagenic pruritus was observed in 41.2% of individuals, mean duration 6.6 ± 8.6 years, and its onset was noticed in the majority of patients (52.4%) before the diagnosis of polycythemia vera. The mean intensity of aquagenic pruritus was 4.8 ± 1.9 points (visual analogue scale). One-third of patients with aquagenic pruritus avoided any contact with water. Antipruritic treatment was received only by 3 patients. Aquagenic pruritus seems to be an important, but frequently neglected, symptom in patients with polycythemia vera.